Determining diagnostic delays in Romanian multiple myeloma patients using the Aarhus statement - Irimia, Ruxandra; Badelita, Sorina; Barbu, Sinziana; Cirlan, Ioana Loredana; Zidaru, Larisa; Coriu, Daniel (Frontiers in Medicine, 2024)
Multiple Myeloma (MM) is classified as one of the hardest cancers to diagnose and the hematological malignancy with the longest diagnostic delays. Although major steps have been made in the improvement of MM patient diagnostic and care, Romanian patients still face long diagnostic delays. So far there have been no studies evaluating the factors associated with diagnostic errors in Romanian MM patients. Using the Aarhus statement, we prospectively determined the diagnostic intervals for 103 patients diagnosed with MM in Fundeni Clinical Institute, between January 2022 and March 2023. Our data unveiled that the main diagnostic delays are experienced during the "patient interval". The patients spend a median of 162 days from the first symptom onset until the first doctor appointment. Bone pain is the most frequent symptom reported by patients (78.64%) but leads to a medical seeking behavior in only half of the reporting patients and determines a median delay of 191 days. The changes in routine lab tests are considered most worrisome for patients leading to a medical appointment after a median of only 25 days. The median primary care interval was 70 days, and the patient had an average of 3.7 medical visits until MM suspicion was first raised. Secondary care interval did not contribute to the diagnostic delays. Overall, the median diagnostic path for multiple myeloma patients in Romania was more than six months, leading to in a higher number of emergency presentations and myeloma-related end organ damage.